Fungsionalisme dan Social Drama (Studi Kasus Kondisi Pendidikan di Indonesia Selama Masa Pandemi COVID-19) - Mayadi, Arya (Jurnal Aktual Pendidikan Indonesia, 2023)
The year 2020 witnessed unprecedented global changes due to the COVID-19 pandemic, profoundly affecting daily life. The education sector, a significant casualty, underwent considerable transformation in Indonesia. Swift government policies highlighted the commitment to prioritize education amid adversity. This study employs both functionalism and Victor Turner's social drama to comprehend the educational shifts during the pandemic. Using a literature review, diverse sources were analyzed through Turner's social drama concept. The pandemic's impact on education unfolded in breach, crisis, redress, and outcome stages. Significant adjustments in learning methods ensued, challenging all stakeholders. A governmental response with new policies aimed to mitigate the crisis. A year later, persistent challenges led to the introduction of the Kurikulum Merdeka. Despite learning disparities, signs of recovery surfaced, attributed to factors like the Kurikulum Merdeka, teacher development, and local government support. While facing challenges, effective implementation of the Kurikulum Merdeka requires comprehensive support. Turner's social drama model provides a nuanced understanding of societal dynamics during crises, complementing functionalism's macro-level focus. Its flexibility enables a productive analysis of societal crises, contributing to a holistic view of societal events.